Parental accounts of sharing an autism spectrum diagnosis with their child: a thematic analysis - Ward, Emma (2014)
The aim of the systematic literature review was to gain an in-depth understanding of how parents of children with an autism spectrum diagnosis experience stigma and in what ways they might manage this. Electronic databases and reference lists of published articles were systematically searched and six qualitative articles were selected for inclusion in the review. Findings from the studies formed the data for a thematic synthesis. Four interconnected themes were identified which capture parents experience of stigma: parent blame/responsibility; hidden disability; diagnosis/label and social isolation/avoidance. A further four themes were identified to highlight ways in which parents may manage this: diagnosis as a weapon; celebrating; increased resilience over time and planning and avoidance. The review suggests that negotiating public spaces may continue to be a challenge for some parents who experience both felt and enacted stigma.